Study of transport properties in superconducting junctions of double insulating barrier (2009)
In this work we analyze the Tomasch effect in double barrier insulating superconducting N1ISIN2 (N: normal metal, I: insulator and S: superconductor) junctions. From the solution of the Bogoliubov–de Gennes equations we find that the differential conductance presents resonances when the applied voltage changes. These resonances are originated by the formation of quasibound states in the superconducting region and depend on the symmetry of the pair potential. We develop an analytical model in order to find the quasibound states energies and its lifetimes. This model allows us to calculate the voltage at which each resonance appears and the resonance widths. We calculate and analyze the dependence of the transmission coefficients with the thickness of the superconducting layer.